Mission in the Spirit : Towards a Pentecostal/Charismatic Missiology - JULIE C. MA;WONSUK MA (Book collections on Project MUSE., 2010)
"The book explores the unique contribution of Pentecostal/Charismatic mission from the beginning of the twentieth century. The first part considers the theological basis of Pentecostal/Charismatic mission thinking and practice. Special attention is paid to the Old Testament, which has been regularly overlooked by the modern Pentecostal/Charismatic movements. The second part discusses major mission topics with contributions and challenges unique to Pentecostal/Charismatic mission. The book concludes with a reflection on the future of this powerful missionary movement. As the authors served as Korean missionaries in Asia, often their missionary experiences in Asia are reflected in their discussions."--Publisher website.